Rethinking Antibiotic Prophylaxis for Spontaneous Bacterial Peritonitis in Patients With Cirrhosis: First, Do No Harm - Markley, J Daniel; Bajaj, Jasmohan S (Clinical infectious diseases, 2025)
Antibiotic prophylaxis for spontaneous bacterial peritonitis (SBPPr) in patients with cirrhosis has been considered the standard of care since the 1990s and is currently recommended by several major gastroenterological societies. However, the evidence that supports this practice is weak, and there is no clear mortality benefit. The unintended consequences of this strategy are not insignificant, both at the patient and population levels. Recent evidence suggests that SBPPr may even cause harm. Since the widespread implementation of SBPPr 3 decades ago, our overall approach to antibiotic use has shifted. We now recognize the growing threat of antimicrobial resistance, the potential harms of antibiotics, and the vital role of antimicrobial stewardship. In light of recent developments and evidence, there is an urgent need for infectious diseases, antimicrobial stewardship, and hepatology leaders to collaborate in development of an updated and cohesive approach to SBPPr.